PENGARUH MOTIVASI DAN IKLIM KERJA TERHADAP KINERJA GURU SMP DI KECAMATAN KELARA KABUPATEN JENEPONTO - Sulaeman Sulaeman (AkMen JURNAL ILMIAH, 2018)
The issues raised in this study were the performance of teacher of junior high school in the district Kelara. Variable research was work motivation, work climate and teacher performance. This study aims to disclose (1) the effect of work motivation on teacher performance (2) influence the working climate together on teacher performance. Based on observation and experience studies, research found that the performance of junior high school teacher in the district Kelara still relatively low. Researchers speculate that the low performance of teachers caused by many factors, among others, teachers d not have the motivation and work climate that is less appropriate. To answer these problem, there were there hypotheses proposed fist there in the influence of work motivation on teacher performance, second, there are climatic influence working on teacher performance, three, there were significant motivation and work climate simultaneously on teacher performance Based on these result, the researchers concluded that there was a positive and significant influence motivation and work climate together on teacher performance. The authors suggest to the relevant parties to increase the motivation of teachers and creating a great work claim so that the teachers performance is better or improved significantly. In addition to these conclusions on board, it is necessary to note the presence of a number of other variables that effect performance such as financial, educational opportunities, career leveling system, promotion, organizational, culture, infrastructure, safety and labor protection were not examined ignored. Guidance to teachers in implementing the work was anhanced. The headmaster in managing school organization in order to make improvement to teachers work motivation, because it will effect the performance of teacher in performing the task. Besides that the working climate of teachers must be cinsided if we want to increase their performance.